Virulence factors attributed to pathogenicity of non albicans Candida species isolated from Human Immunodeficiency virus infected patients with oropharyngeal candidiasis. - Deorukhkar, Sachin Chandrakant; Saini, Santosh (Annals of Pathology and Laboratory Medicine, 2015)
Background: Oropharyngeal candidiasis (OPC) is the most common opportunistic mycoses among HIV infected patients. Although Candida albicans is the most common aetiological agent of OPC, in recent years non albicans Candida (NAC) species have become increasingly prominent pathogens. As compared to C. albicans, NAC spp. often demonstrates low susceptibility to commonly used antifungal drugs. Aim: The present study was conducted with an aim to determine the expression of virulence factors of NAC spp. isolated from HIV infected patients with OPC. Methods: A total of 123 NAC spp. isolated from HIV infected patients with OPC were included in the study. The virulence factors studied were adherence to buccal epithelial cell, exoenzymatic activity and haemolytic activities. Results: C. glabrata and C. tropicalis were predominant isolates from NAC spp. ABEC was more in C. dubliniensis isolates. As compared to other NAC spp. C. glabrata demonstrated low ABEC. High phospholipase activity was noted in C. tropicalis followed by C. kefyr. Proteinase activity was high in C. dubliniensis followed by C. tropicalis. Haemolysin production was high in C. tropicalis followed by C. kefyr isolates. Conclusion: NAC spp. once overlooked as mere contaminants or non pathogenic commensals have emerged as potent pathogens. These isolates are capable of producing virulence factors once attributed only to C. albicans. Knowledge of these virulence factors is important for understanding the pathogenesis of candidiasis and will help to explore new antimycotic drug targets for improved therapeutic regimens.